2005
DOI: 10.1080/14786410410001704822
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial terpenoids fromPterocarpus indicus

Abstract: A mixture of loliolide 1 (> 85%) and paniculatadiol 2 (< 15%) was obtained from the ethyl acetate leaf extract of Pterocarpus indicus by silica gel chromatography, while the air-dried flowers afforded lupeol 3 and phytol esters 4. The structures of 1-4 were determined by NMR spectroscopy. Antimicrobial tests on a mixture of 1 and 2 indicated that it has moderate activity against Candida albicans and low activity against Pseudomonas aeruginosa, Escherichia coli, and Aspergillus niger. It was found inactive agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Though, alkaloids, phenolic compounds and flavonoids were present in limited amount. Each of this group of compounds has been reported to possess antimicrobial activity (Ragasa et al, 2005;Cuhnie and Lamb, 2006;Soetan et al, 2006) and reportedly exert their effects by affecting the cell membrane integrity of the bacteria (Hendrich, 2006;Trombetta et al, 2005;Killeen et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Though, alkaloids, phenolic compounds and flavonoids were present in limited amount. Each of this group of compounds has been reported to possess antimicrobial activity (Ragasa et al, 2005;Cuhnie and Lamb, 2006;Soetan et al, 2006) and reportedly exert their effects by affecting the cell membrane integrity of the bacteria (Hendrich, 2006;Trombetta et al, 2005;Killeen et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Roxb-(−)-epicatechin, a water soluble benzopyran, stimulates insulin secretion (Hii and Howell, 1984). In addition, the biological activities of crude extracts of Pterocarpus species include hypoglycaemic and antidiabetic properties (Pterocarpus marsupium (Abesundara et al, 2004;Saxena and Vikram, 2004;Vats et al, 2004;Anandharajan et al, 2005;Dhanabal et al, 2006), Pterocarpus santalinus (Nagaraju et al, 1991;Kameswara Rao et al, 2001)) and also, cardiotonic activity (Pterocarpus marsupium (Mohire et al, 2007)), antimicrobial activity (Pterocarpus santalinus (Narayan et al, 2007); Pterocarpus angolensis (Steenkamp et al, 2004;Sami et al, 2009); Pterocarpus indicus (Ragasa et al, 2005)), antiulcerogenic activity (Pterocarpus santalinus (Narayan et al, 2007)). Methanolic extracts of Pterocarpus santalinus have also been reported to induce apoptosis of cancer HeLa cells (Kwon et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…One photosensitizer is chlorophyll which can be obtained from leaf extract [7]. Chlorophyll from Pterocarpus indicus was made as an antimicrobial drug [11]. This showed that adding chlorophyll was able to decrease colony, although it was not different with no treatment colony.…”
Section: Resultsmentioning
confidence: 99%